Faktor-Faktor yang mempengaruhi Pembangunan Kerjaya Wanita Dalam Sektor Akademik - Nor Sarmila, Ishak (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Generally, this study is about factor that influences women career development in academic sectors. It consists of motivation factors, family courage, ethics programs and development. This study also includes demography factors such ac age, services duration, and marital status. Therefore, this study uses questionaire for in order to get responds from 76 respondents that consist of female teacher from 10 different schools around Kuching town. The author used descriptive methods that are to describe all the information in term of frequency or parent of demography factors. Statistical information from Pearson correlation text has been used in order study the hypothesis between has been used in order study the hypothesis between different demography factors involved such as age, marital status. From the evaluation, it is found that demography factor has significant relation with motivation and training factor but do not have significant relation with factors. Based on evaluations and analyzed results, the authors drawn some conclusions and recommendations for the future researchers.